Estimating the limiting viscosity number of crude natural rubber - Ehabe E; Gobina M S; Le Roux Y; Ngolemasango F; Sainte-Beuve J (Proceedings of IRRDB Symposium 1999, Hainan, Peoples Republic of China. pp.413-422., 1999)
The effect of certain techniques employed in viscosity-average molecular mass determination of raw natural rubber on the precision and interpretation of the results, were investigated. Rubber solutions, even when protected with an antioxidant should be stored in the dark, that is if abnormally high Huggins k coefficients must be avoided. Solutions of 0.25 - 2.0 g/dm3 were most suitable fo [n] measurement. The use of solutions more dilute than 0.25 g/dm3 reduced the coefficient of determination of the simple linear best-fit characterising the distribution of viscosity number as a function of solution concentration determination. The presence of gel in the solutions greatly increased the limiting viscosity number and reduced the k parameter when compared to measurements on the sol fractions only. The use of modified apparent concentration values to compensate for the presence of gel, since the gel normally does not contribute to concentration effects, did not improve the precision of the test. A significantly negative correlation was confirmed between [n] and k. The Huggins and Schulz Blaschke equations produced more reproducible limiting viscosity numbers relative to the Kraemer and Peterlins equations. The Huggins equation produced the lowest [n] values. The correlation coefficient of the best-fit linear equation seemed to improve for samples of higher limiting viscosity numbers, indicating a possible bias of this model for higher molecular mass rubbers.
Keywords: Gel fraction; Intrinsic viscosity; Molecular mass; Natural rubber; Sol fraction